The influence of nutritional history on the functional response of Geocoris pallidipennis to its prey, Myzus persicae. Issue 6 (December 2014) - Liu, F.; Zeng, F.
Abstract Insect artificial diets are the foundation for mass production of insect predators. Whether there is an influence of long-term rearing with artificial diet on the control ability of predators should be considered. Here, we focused on the effect of nutritional history on the functional response of Geocoris pallidipennis to Myzus persicae. The influence of nutritional history (artificial diet versus natural prey, M. persicae) on the functional response of third to fifth instar nymphs and female G. pallidipennis was examined in the laboratory. The results showed that the functional response curve of both the nymphs and the adult female of G. pallidipennis to M. persicae reflected similar trends on both nutritional histories and confirmed the type II response. Adult female G. pallidipennis reared on either M. persicae or artificial diet produced a significantly better performance than the juvenile stages tested. We estimated that adult female G. pallidipennis can consume 141.6 (artificial diet) or 131.6 (M. persicae) aphids per day, respectively. This indicated that G. pallidipennis reared on both artificial diet and M. persicae displayed high rates of predation.